Musculoskeletal modelling of elite handcycling motion: evaluation of muscular on- and offset - Felsner, E.-M.; Litzenberger, S.; Mally, F.; Sabo, A. (Procedia Engineering, 2016)
Handcycling, as a competitive sport, has been a Paralympic discipline since 2004 and is performed by handicapped athletes with impairments of the spine or brain. In this work a musculoskeletal model of a handcyclist is developed in the software AnyBody using kinematic data from a previous study of handcycling of one male elite handbiker (class: H3.2). The on- and offset timing of several muscles of the upper body (left and right of: m. pectoralis, m. deltoideus, m. biceps brachii and m. triceps brachii) were calculated with different thresholds and compared to results from surface electromyography (sEMG) measurements recorded during the previously mentioned subject study. It could be shown, that the mean overlap of muscle activation times was between a satisfying 64% and 75% depending on the threshold used. However, especially for m. deltoideus a very different on- offset behaviour was observed in the simulation than in the sEMG measurements resulting from the positioning of the electrodes in the subject study on one specific branch of the m. deltoideus and insufficient knowledge about the actual course of the crank torque for this specific athlete. Thus given sufficient accuracy of input parameters - musculoskeletal modelling could be used to predict changes in muscle activity timing for different handcycle setups.